Transformasi Pendidikan: Analisis Kemampuan Guru Ekonomi Mengadaptasi Media Berbasis Teknologi Di Era Digital - Wati, Indah; Novita, Yulia; Nabil, Muhammad Deven; Sukirno, Sukirno (Universitas Batanghari Jambi, 2026)
This study aims to analyze economics teachers ability to adapt technology-based learning media in the digital era and to identify the constraints and efforts involved in its implementation. The study employed a convergent mixed-methods design involving six economics teachers at SMA Negeri 4 Pekanbaru selected purposively. Quantitative data were collected through a questionnaire developed from DigCompEdu indicators and supported by validated and reliable instruments, while qualitative data were obtained through interviews and observations. The findings reveal that teachers ability to adapt technology-based media is in the very good category, reaching an overall score of 80.86%. Specifically, professional engagement reached 82.92%, digital resources 77.31%, teaching and learning 84.03%, assessment 79.17%, empowering learners 77.24%, and facilitating learners digital competence 84.09%. The main constraints were unstable internet access, limited device storage, and the need to adjust to newly introduced applications. The efforts undertaken include the use of multiple digital platforms, school-level provision of supporting infrastructure, and participation in technology-related professional development. These findings indicate that technology integration in economics learning has progressed positively; however, stronger infrastructure support and sustained professional development remain necessary to ensure more meaningful, interactive, and contextual technology use in classroom practice.